Pedagogía Cognitiva: la educación y el estudio de la mente en la Sociedad de la Información - Gonzalo VÁZQUEZ GÓMEZ; Fernando BÁRCENA ORBE (Ediciones Universidad de Salamanca, 2016)
This paper support that contemporary Information's Society required a new conception of education and human learning. This learning respond to a new cultural design based on human brain, conceived as a complex system. Cognitive Pedagogy interrogue on nature of activity of mind and operation of cognitives process in relation to processing of information, problem-solving and intentional mental state's attribution. In this sens, adequates theories of mind are necessaries to explain questions such as: propositive's action and self-regulated; body-mind and mind-mind relationship. and so on. This study treat on cognitives sciences and the situation of Pedagogy into this sciences. Finally, the paper propose certain consequences to educational activity and pedagogical research.